Industri Bubuk Kopi Cap Matahari di Panti Kecamatan Panti Kabupaten Pasaman (1978 – 2021) - Nuri Gusmarini; Azmi Fitrisia (Jurusan Sejarah FIS UNP, 2022)
This research is a historical study that examines Bubuk Kopi Cap Matahari Industry in the Panti District, Panti District, Pasaman Regency (1978-2021). The purpuse of this study is to describe the origins of the establisment of the sun stanmped coffee powder home industry, its devolopment and describe the strategies used by Bubuk Kopi Cap Matahari Industry to survive. This study uses the historical method through four stages, namely heuristics, source criticism, interpretation and historiography. The results of the study show that Bubuk Kopi Cap Matahari Industry was founded in 1978 and has experienced developments and declines that can be overcome by this Bubuk Kopi Cap Matahari business so that it can survive until now. Keywords: Bubuk Kopi Cap Matahari Industry, Development, Strategy